Insuficiência Cardíaca na Miocardiopatia Hipertrófica: Preditores, Manifestações Clínicas e Tratamento - Ana Margarida Esteves Cardoso (2022)
Scientific and technological advances in hypertrophic cardiomyopathy (HCM) have allowed HCM transitioning from being a common cause of sudden cardiac death in adolescents and young adults to a chronic disease affecting middle-aged and elderly individuals, with an increase of the prevalence of heart failure (HF). Nevertheless, there are still no established prognostic factors for HF risk stratification, nor specific therapies for this entity, that have an huge impact on patients' health. This review intends to highlight the growing importance of HF phenotype in the last decades and the need of improving HF and HCM patients' management.